Attempted vaginal birth after cesarean: assessment of morbidity and predictors of success - Rocio Garcia-Jimenez; Irene Valero; Ana M. Weber-Fernandez; Natalia Florez; Irene Martinez-Aguado; Carlota Borrero (Permanyer, 2022)
Objective: Determining the appropriate approach for delivery after previous cesarean is a very controversial issue. Our objective was to establish whether pregnant women with a previous cesarean have an increased maternal and fetal morbidity and mortality after attempting vaginal delivery as well as to determine which factors may influence the achievement of a vaginal birth after cesarean. Materials and methods: A retrospective observational cohort study including 390 patients (196 cesarean group and 194 nulliparous group) was carried out. We compared neonatal and maternal outcomes between groups. Afterward, a multivariate logistic regression was applied for our second objective. Results: There were higher rates of uterine rupture (2% vs. 0%, p: 0.045) and puerperal hemorrhage (9.7% vs. 3.1%, p: 0.008) in the cesarean group and lower vaginal delivery rate (58.2% vs. 77.8%, p < 0.0005). We found that the induced onset of labor (OR = 2.9) and new born weight (OR = 1.0001) were associated with an increased risk of cesarean section. Conclusions: Our findings stress the need for further investigations in this field, which might provide a basis for a better management of patients with a previous cesarean.